The role of visual metonymy in leadership symbolism: Mapping its dynamics through the Sphinx. (August 2019) - Riad, Sally
Despite the long-standing relevance of symbols in culture studies on leadership, research has rarely examined significations of leadership through metonymy, an important trope that pervades symbolism but is often overlooked. This paper offers a typology of visual metonymy that outlines forms pertinent to leadership. The study draws on the Sphinx in cultural history to map out various metonymies and chart their dynamics. It then traces these metonymies in historical and recent political cartoons on leadership in contexts of colonization, nation building, and revolution. The work also delineates patterns in composite metonymy and its combination with metaphor. Metonymy has paradoxical effects on the discursive construction of leadership, both maintaining and changing extant values and views. So visual metonymy facilitates iconoclasm, the destruction of images or statues, based on shifts in value judgments of leadership and its symbols. These findings compel us to think differently about symbolism and leadership. They show how a symbol's meaning and value are positional and provisional, temporarily located within multiple relationships and realities. Similarly, leadership is wrought through positionality and provisionality, constantly reshaped by various contextual positions and contingent relationships that render it inherently fluid and contested. The paper further contributes to theorization on leadership by offering new grounds for its visual analysis and a fresh perspective through which to explore its embodiment. Altogether, the work instigates us to rethink extant adages on "leaders using symbols" and "leaders as symbols." It calls for research on leadership that supplements the interest in symbols with an emphasis on symbolization.